WCFL: Chicago's Voice of Labor, 1926-78 - Webb, Jeff A. (Labour / Le Travail, 1998)
The article reviews the book, "[Chicago Radio Station] WCFL: Chicago's Voice of Labor, 1926-78," by Nathan Godfried.